Fuzzy Edge Detection Using Fuzzy C-Means Thresholding for MRI Brain Image - Tamilmani, N; Kirubakaran, C; Senthilkumaran, N (International Journal of Computer Sciences and Engineering, 2025)
In this paper, the work aimed a robust edge detection based on fuzzy technique for MRI brain image. Segmentation is the critical task in medical applications and also it is the most important task in medical image analysis. In brain image, segmentation is commonly used for analyse the brain changes and structure of the brain image and analyse the region of the brain image. Edge detection is the basic tool for segmentation. Edge detection is the finding the boundary of the particular image and edges occur on the boundary between the object and the background. Here, this paper segments the MRI image using fuzzy c-means thresholding. It covert the grey image to binary image and the result image applied fuzzy interface system and find edge of the particular object in the MRI Image. Experiments were done by using the MRI scan images